AID-I Great Lakes Regional Learning Event - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
We’re thrilled to announce we’ve attained an exciting milestone – AID-I Great Lakes is in late mid-life, at all of 1.5 years old!